Exploring adaptations to the modified shuttle walking test. Issue 5 (22nd May 2013) - Woolf-May, Kate; Meadows, Steve
Abstract : Objective: The 10 m modified shuttle walking test (MSWT) is recommended to determine the functional capacity in older individuals and for patients entering cardiac rehabilitation. Participants are required to negotiate around cones set 1 m from the end markers. However, consistent comments indicate that for some individuals manoeuvring around the cones can be quite difficult. Therefore, the objective of this study was to explore differences within and between non-cardiac and postmyocardial infarction (MI) males during MSWT with and without the cones. Design: Comparative study. Participants: 20 post-MI (64.8±6.6, range 51–74 years) and 20 non-cardiac male controls (64.1±5.7, range 52–74 years) participated. Methods: Participants performed MSWT with and without cones. Throughout, the participants expired air, and the heart rate (bpm) (HR) and ratings of perceived exertion (RPE) were measured. Participant protocol preference was recorded verbatim. Results: One-way analysis of variance found no significant difference in VO2 peak (cones 20.4±5.1 vs no-cones 21.9±4.8 ml/kg/min, p=0.197) or distance ambulated (cones 631.8±132.9 m vs no-cones 662.4±164.1 m, p=0.371) between protocols or groups. Analysis comparing lines of regression showed a significant trajectory difference in VO2 (ml/kg/min) (p<0.01) between protocols with higher HR (p<0.01) and respiratory exchange ratio (RER, p<0.001) values during cones. RPEs were higher for post-MIs versus controls during both protocols (p<0.05). Post-MIs taking β-blockers produce significantly lower HR values. The χ 2 analysis found no significant difference in protocol preference (no-cones: all n=25, 63%; post-MIs n=13, 65%; and controls n=12, 60%). Conclusions: Post-MIs found both protocols subjectively harder than controls with no significant difference in the VO2 peak. However, both groups worked at a lesser percentage of their anaerobic threshold during no-cones protocol as indicated by lower RER values. Importantly, for the post-MIs, this would reduce their risk of functional impairment. Therefore, though more research is required, indicators at present are more favourable for the use of the no-cones with post-MIs.